The Effect of the Electoral Calendar on Politicians' Selection into Legislative Cohorts and Legislative Behavior in Argentina, 1983–2007. Issue 4 (24th May 2016) - Lucardi, Adrián; Micozzi, Juan Pablo
Abstract : How do electoral opportunities affect politicians' career strategies? Do politicians behave strategically in response to the opportunities provided by the electoral calendar? We argue that in a legislature that combines nonstatic ambition with a staggered electoral calendar, different kinds of politicians will have dissimilar preferences towards running in concurrent or midterm elections. More specifically, politicians with no previous executive experience should strategically run in midterm legislative elections in order to increase their visibility among voters, while more experienced politicians should opt for concurrent elections. We support these claims with data from the Argentine Chamber of Deputies between 1983 and 2007.